High-strength and high-toughness polyolefin badminton bionic feather composite material and preparation method thereof

By combining high-crystalline polypropylene material, talc powder and high-rigid glass fibers, high-strength and high-toughness composite materials, the existing badmintons have solved the problems of low punch resistance and insufficient toughness, extended their service life and have cheap molding and processing and the advantages of recyclable.

CN119307040APending Publication Date: 2025-01-14HEFEI PULILON POLYMER MATERIALS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411570191.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing polymer synthetic materials badminton have low punch resistance, are prone to rupture, and are not tough enough, resulting in a short service life.

Method used

High crystallinity polypropylene material is combined with high silicon content talc powder and high rigidity glass fiber, and the silane coupling agent film is wrapped by vacuum deposition method, and uniformly mixed and molded in a twin-screw extruder to form high strength and high strength Tough composite material.

Benefits of technology

It improves the weather resistance, punch resistance and toughness of badminton, extends its service life, and has the advantages of cheap molding and recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005120262290000021
    Figure BDA0005120262290000021
  • Figure BDA0005120262290000061
    Figure BDA0005120262290000061
  • Figure BDA0005120262290000062
    Figure BDA0005120262290000062
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, in particular to a high-strength and high-toughness polyolefin badminton bionic feather composite material and a preparation method thereof.The preparation method comprises the steps that high-crystallinity and high-regularity polyolefin is added with a certain proportion of customized glass fibers with the specific length-diameter ratio, talcum powder with the high silicon content and auxiliaries; therefore, the composite material capable of being subjected to thermoplastic molding is prepared. In the project, the length-diameter ratio of the glass fibers and the microstructure of the glass fibers and the high-silicon talcum powder which are finally kept in the material are adjusted through the screw combination, and the high-molecular bionic feather material which is high in strength and toughness and can be recycled is prepared. Feather formed by injection molding of the material has the multiple advantages of being convenient to mold and process, high in flight stability, excellent in mechanical property, resistant to beating and falling, not prone to damage, environmentally friendly, capable of being recycled and the like. The market popularization value is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a composite material of high-strength and high-toughness polyolefin badminton bionic feathers and a preparation method thereof. Background Art

[0002] Badminton is a sport that is open to all people and is accepted and loved by the general public. Traditional badminton consists of 16 feathers (duck or goose feathers) fixed on the ball holder. Through trimming, the shape of each feather on each ball is basically the same, and then the 16 feathers are arranged into a truncated cone shape. However, in badminton, the service life of the badminton is usually not long, and the feathers are easily scattered, broken, and damaged, making it unusable.

[0003] In order to extend the life of badminton, badminton made of polymer synthetic materials has appeared on the market, such as a method of improving the compatibility of nylon and glass microbeads disclosed in patent document No. CN103467981B (announcement date: August 17, 2016).

[0004] However, the existing polymer synthetic material badminton still has the problems of low striking strength, easy to break, insufficient toughness and the like. To this end, a high-strength and high-toughness polyolefin badminton bionic feather composite material and a preparation method are provided. The composite material is cheap, easier to shape and process, and has better weather resistance, striking strength and toughness, and is more in line with market demand. Summary of the invention

[0005] The purpose of the present invention is to provide a high-strength and high-toughness polyolefin badminton bionic feather composite material and a preparation method, aiming to solve the problems of existing polymer synthetic material badminton such as low striking strength, easy breakage, insufficient toughness, etc.

[0006] The embodiment of the present invention is implemented as follows: a composite material of high-strength and high-toughness polyolefin badminton bionic feathers includes an additive package, a high-crystallinity polypropylene material and talcum powder, the additive package includes 0.1-0.2 parts of pentaerythritol ester antioxidant, 0.1-0.2 parts of phosphite antioxidant, 0.2-1 parts of silicone powder, 0.1-0.2 parts of ultraviolet absorber, 0.1-0.2 parts of light stabilizer, 0.3-0.5 parts of polyolefin special rigidity nucleating agent, 0-6 parts of polyolefin grafted maleic anhydride, and the materials are calculated as 100 parts.

[0007] Preferably, the high crystallinity polypropylene material needs to be placed in a vacuum dehumidification drying oven for drying, the temperature of the drying oven is 90-100° C., and the drying time is 4-6 hours.

[0008] Preferably, the high crystallinity polypropylene has the following properties:

[0009]

[0010] Preferably, the particle size of talc D90 is 0.5-1 micron and the silicon dioxide content is 60-65%.

[0011] Preferably, high-rigidity glass fibers are also included, and the high-rigidity glass fibers have a length of 3 mm and a diameter of 10 μm.

[0012] A method for preparing high-strength and high-toughness polyolefin badminton bionic feathers comprises the following steps:

[0013] S1: equipped with additive package;

[0014] S2: Mix the preferred high crystallinity polypropylene material, high silicon content and high mesh talc powder and the additive package in a high-speed mixer at a certain mass ratio;

[0015] S3: Take a certain amount of high-rigidity glass fiber and evenly wrap a layer of silane coupling agent film on its surface by vacuum deposition method;

[0016] S4: Adjust the twin-screw combination sequence so that all the mixed materials can be evenly dispersed, and the length of the glass fiber can be kept between 400-500 microns, so that it is compatible with the talc powder with an average particle size of 0.5 microns, forming a microscopic synergistic strengthening and toughening effect in the polypropylene resin;

[0017] S5: Put the evenly mixed materials into a parallel co-rotating twin-screw extruder, feed high-rigidity glass fiber with special surface treatment from the specific area side feeding, adjust the feeding speed, the temperatures from the first zone to the eleventh zone are 170℃, 190℃, 200℃, 210℃, 220℃, 220℃, 220℃, 210℃, 200℃, 190℃, 190℃, the die head is 220℃, the speed is 280r / min, and after melting, extrude, draw and granulate to obtain the finished bionic badminton feather composite material.

[0018] A high-strength and high-toughness polyolefin badminton bionic feather composite material and a preparation method thereof provided in an embodiment of the present invention:

[0019] The preparation method is a thermoplastic composite material obtained by adding a certain proportion of customized glass fiber with a specific aspect ratio, talc with a high silicon content, and additives to a high-crystallinity, high-regularity polyolefin. In this project, the aspect ratio of the glass fiber finally retained in the material, as well as the microstructure of the glass fiber and high-silicon talc, are adjusted by screw combination to obtain a high-strength, high-toughness, and recyclable polymer bionic feather material. The feathers formed by injection molding of this material have multiple advantages such as easy molding and processing, strong flight stability, excellent mechanical properties, resistance to impact and fall, not easy to damage, environmental protection, and recyclability. It has market promotion value. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and test result tables. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0021] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0022] Implementation Case 1

[0023] Step 1: Prepare the additive package. Take 0.1kg of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.2kg of tris[2.4-di-tert-butylphenyl]phosphite, 0.5kg of silicone masterbatch, 0.4kg of polypropylene special rigidity enhancing nucleating agent, 0.1kg of light stabilizer, and 0.2kg of ultraviolet absorber, put them together in a high-speed mixing pot and mix at high speed for 10 minutes to obtain an additive package.

[0024] Step 2: Take 84 kg of the preferred high crystallinity polypropylene material, 14 kg of high silicon content and high mesh talc powder, and 2 kg of the additive package obtained in step 1, add them into a high-speed and low-speed mixer and mix them evenly to obtain the material 1 to be used. (The polypropylene material used is Sinopec M30RHC. The high silicon content and high mesh talc powder used has a D90 of 0.5 microns and a silicon dioxide content of 65%).

[0025] Step 3: Adjust the twin-screw assembly sequence so that it can disperse all the mixed materials evenly.

[0026] Step 4: Feed the material 1 to be used from the main feeding port of the twin-screw extruder. Adjust the feeding speed, the temperature of each zone is 170℃, 190℃, 200℃, 210℃, 220℃, 220℃, 220℃, 210℃, 200℃, 190℃, 190℃, the head is 220℃, and after melting, extrude, draw and granulate to obtain the finished badminton bionic feather composite material.

[0027] Implementation Case 2

[0028] Step 1: Prepare the additive package. Take 0.1kg of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.2kg of tris[2.4-di-tert-butylphenyl]phosphite, 0.5kg of silicone powder, 0.4kg of polypropylene special rigidity enhancing nucleating agent, 0.2kg of ultraviolet absorber, 0.1kg of light stabilizer, and 0.5kg of silane coupling agent, put them together in a high-speed mixing pot and mix at high speed for 10 minutes to obtain the additive package.

[0029] Step 2: Take 72.3 kg of the preferred high crystallinity polypropylene material, 25 kg of high silicon content and high mesh talc powder, and 2.7 kg of the additive package obtained in step 1, add them into a high-speed and low-speed mixer and mix them evenly to obtain the material 1 to be used. (The polypropylene material used is Sinopec M30RHC. The high silicon content and high mesh talc powder used has a D90 of 0.5 microns and a silicon dioxide content of 65%).

[0030] Step 3: Adjust the twin-screw assembly sequence so that it can disperse all the mixed materials evenly.

[0031] Step 4: Feed the material 1 to be used from the main feeding port of the twin-screw extruder. Adjust the feeding speed, the temperature of each zone is 170℃, 190℃, 200℃, 210℃, 220℃, 220℃, 220℃, 210℃, 200℃, 190℃, 190℃, the head is 220℃, and after melting, extrude, draw and granulate to obtain the finished badminton bionic feather composite material.

[0032] Implementation Case 3

[0033] Step 1: Prepare the additive package. Take 0.1kg of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 0.2kg of tris[2.4-di-tert-butylphenyl] phosphite, 0.3kg of TAF, a lubricant to prevent glass fiber exposure, 0.8kg of silicone powder, 0.5kg of a special rigidity-enhancing nucleating agent for polypropylene, 0.2kg of a UV absorber, 0.1kg of a light stabilizer, and 3.8kg of polypropylene grafted maleic anhydride, and put them into a high-speed mixing pot and mix them for 10 minutes to obtain an additive package.

[0034] Step 2: Take 75 kg of the preferred high crystallinity polypropylene material, 2.5 kg of high silicon content and high mesh talc powder, and 6 kg of the additive package obtained in step 1, add them into a high-speed and low-speed mixer and mix them evenly to obtain the material 1 to be used. (The polypropylene material used is. The high silicon content and high mesh talc powder used is small stone, D90 is 0.5 microns, and the silicon content is.)

[0035] Step 3: Take 16.5 kg of high-rigidity glass fiber with a length of 3 mm and a diameter of 10 μm, and use vacuum deposition to evenly coat the surface with a layer of silane coupling agent film. After drying, the second material to be used is obtained.

[0036] Step 4: Adjust the twin-screw assembly sequence so that all the mixed materials can be evenly dispersed, and the length of the glass fiber can be kept between 400-500 microns, so that it can be compatible with talcum powder with an average particle size of 0.5 microns, forming a microscopic synergistic strengthening and toughening effect in the polypropylene resin.

[0037] Step 5: Feed the first material to be used from the main feeding port of the twin-screw extruder, and feed the second material to be used from the side feeding port of the fifth zone of the twin-screw extruder. Adjust the feeding speed, the temperature of each zone is 170℃, 190℃, 210℃, 210℃, 220℃, 210℃, 200℃, 190℃, 190℃, 190℃, 210℃, the die head is 220℃, and after melting, it is extruded, stretched, and granulated to obtain a finished bionic badminton feather composite material.

[0038] Implementation Case 4

[0039] Step 1: Prepare the additive package. Take 0.1kg of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.2kg of tris[2.4-di-tert-butylphenyl]phosphite, 1kg of silicone powder, 0.5kg of polypropylene special rigidity enhancing nucleating agent, 0.2kg of ultraviolet absorber, 0.1kg of light stabilizer, and 2.5kg of polypropylene grafted maleic anhydride, put them together in a high-speed mixing pot and mix at high speed for 10 minutes to obtain the additive package.

[0040] Step 2: Take 74 kg of the preferred high crystallinity polypropylene material, 8.2 kg of high silicon content and high mesh talc powder, and 5.8 kg of the additive package obtained in step 1, add them into a high-speed and low-speed mixer and mix them evenly to obtain the material 1 to be used. (The polypropylene material used is. The high silicon content and high mesh talc powder used is small stone, D90 is 0.5 microns, and the silicon content is.)

[0041] Step 3: Take 12 kg of high-rigidity glass fiber with a length of 3 mm and a diameter of 10 microns, and use vacuum deposition to evenly coat the surface with a layer of silane coupling agent film. After drying, the second material to be used is obtained.

[0042] Step 4: Adjust the twin-screw assembly sequence so that all the mixed materials can be evenly dispersed, and the length of the glass fiber can be kept between 400-500 microns, so that it can be compatible with talcum powder with an average particle size of 0.5 microns, forming a microscopic synergistic strengthening and toughening effect in the polypropylene resin.

[0043] Step 5: Feed the first material to be used from the main feeding port of the twin-screw extruder, and feed the second material to be used from the side feeding port of the fifth zone of the twin-screw extruder. Adjust the feeding speed, the temperature of each zone is 170℃, 190℃, 210℃, 210℃, 220℃, 210℃, 200℃, 190℃, 190℃, 190℃, 210℃, the die head is 220℃, and after melting, it is extruded, stretched, and granulated to obtain a finished bionic badminton feather composite material.

[0044] The composite materials obtained in the above embodiments and comparative examples were tested for relevant indicators, wherein the tensile strength was tested according to GB / T1040-2006, the tear strength was tested according to QB / T1130-1991, and the elongation at break was also tested according to GB / T1040-2006. The test results are shown in the following table:

[0045] Implementation Case 1

[0046]

[0047] Implementation Case 2

[0048]

[0049]

[0050] Implementation Case 3

[0051]

[0052] Implementation Case 4

[0053]

[0054] From the test results of the above implementation cases, it can be concluded that after increasing and adjusting the ratio of glass fiber and talcum powder, the strength and impact resistance of the material are significantly improved.

Claims

1. A high-strength and high-toughness polyolefin badminton bionic feather composite material, characterized in that: It includes an additive package, a high-crystallinity polypropylene material and talcum powder. The additive package includes 0.1-0.2 parts of pentaerythritol ester antioxidant, 0.1-0.2 parts of phosphite antioxidant, 0.2-1 parts of silicone powder, 0.1-0.2 parts of ultraviolet absorber, 0.1-0.2 parts of light stabilizer, 0.3-0.5 parts of polyolefin special rigidity nucleating agent, 0-6 parts of polyolefin grafted maleic anhydride, and the materials are calculated based on 100 parts.

2. The high-strength and high-toughness polyolefin badminton bionic feather composite material according to claim 1, characterized in that: The high crystallinity polypropylene material needs to be placed in a vacuum dehumidification drying oven for drying first, the temperature of the drying oven is 90-100° C., and the drying time is 4-6 hours.

3. The high-strength and high-toughness polyolefin badminton bionic feather composite material and preparation method according to claim 2, characterized in that: High crystallinity polypropylene properties:

4. The high-strength and high-toughness polyolefin badminton bionic feather composite material according to claim 1, characterized in that: The particle size of talcum powder D90 is 0.5-1 micron and the silicon dioxide content is 60-65%.

5. The high-strength and high-toughness polyolefin badminton bionic feather composite material according to claim 1, characterized in that: Also included are high-rigidity glass fibers, which are 3 mm in length and 10 microns in diameter.

6. The method for preparing high-strength and high-toughness polyolefin badminton bionic feathers according to claim 1, characterized in that: The following steps are involved: S1: equipped with additive package; S2: Mix the preferred high crystallinity polypropylene material, high silicon content and high mesh talc powder and the additive package in a high-speed mixer at a certain mass ratio; S3: Take a certain amount of high-rigidity glass fiber and evenly wrap a layer of silane coupling agent film on its surface by vacuum deposition method; S4: Adjust the twin-screw combination sequence so that all the mixed materials can be evenly dispersed, and the length of the glass fiber can be kept between 400-500 microns, so that it is compatible with the talc powder with an average particle size of 0.5 microns, forming a microscopic synergistic strengthening and toughening effect in the polypropylene resin; S5: Put the evenly mixed materials into a parallel co-rotating twin-screw extruder, feed high-rigidity glass fiber with special surface treatment from the specific area side feeding, adjust the feeding speed, the temperatures from the first zone to the eleventh zone are 170℃, 190℃, 200℃, 210℃, 220℃, 220℃, 220℃, 210℃, 200℃, 190℃, 190℃, the die head is 220℃, the speed is 280r / min, and after melting, it is extruded, stretched, and granulated to obtain a finished bionic badminton feather composite material.

Citation Information

Patent Citations

  • A method to improve the compatibility of nylon with glass microspheres

    CN103467981B